2015
DOI: 10.1007/s00595-015-1246-8
|View full text |Cite
|
Sign up to set email alerts
|

A clinical trial of autologous adipose-derived regenerative cell transplantation for a postoperative enterocutaneous fistula

Abstract: Transplantation of autologous ADRCs is safe, feasible and advantageous, as it can secure a sufficient cell count without culture or multiple passages, and will likely be effective for a postoperative enterocutaneous fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
(37 reference statements)
0
18
0
5
Order By: Relevance
“…Almost all organ system have been implicated in adipose‐derived cell therapy. The indication for treatment in the included studies was (in order count) soft tissue , gastrointestinal , musculoskeletal , rheumatological , ulcer/ischemic limb , urogenital , cardiac , neurological , immunological , pulmonary , and ophthalmological (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Almost all organ system have been implicated in adipose‐derived cell therapy. The indication for treatment in the included studies was (in order count) soft tissue , gastrointestinal , musculoskeletal , rheumatological , ulcer/ischemic limb , urogenital , cardiac , neurological , immunological , pulmonary , and ophthalmological (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…Almost all organ system have been implicated in adipose-derived cell therapy. The indication for treatment in the included studies was (in order count) soft tissue www.StemCellsTM.com [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], gastrointestinal [8,[36][37][38][39][40][41][42][43][44][45][46][47][48], musculoskeletal [49][50][51][52][53][54][55][56][57][58], rheumatological [59][60][61][62][63], ulcer/ischemic limb [64][65][66][67], urogen...…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…UADSCs are the nonbuoyant cellular fraction containing several types of stem and regenerative cells, including ADSCs, vessel‐forming cells, such as endothelial and smooth muscle cells, and preadipocytes . In the previous clinical study, UADSC has been reported to be safe, feasible and advantageous, as it can secure a sufficient cell count without culture or multiple passages, compared with ADSC …”
mentioning
confidence: 99%
“…18 In the previous clinical study, UADSC has been reported to be safe, feasible and advantageous, as it can secure a sufficient cell count without culture or multiple passages, compared with ADSC. 19 There is insufficient evidence supporting the effectiveness of UADSC for OA despite the general perception regarding their potential for becoming an alternative cell-based treatment modality. Recent studies have reported that the paracrine effect of ADSCs on chondrocytes is the key contributor for the suppressive effects of OA development in a rabbit model.…”
mentioning
confidence: 99%